Incidencia del trabajo informal en la economía familiar de los habitantes de la ciudadela Cristina maría del cantón El Guabo en el año 2014- 2015. - Armijos Maldonado, Antonio Agustín (2015)
The present work graduated with a title, IMPACT OF INFORMAL WORKING IN THE FAMILY ECONOMY OF THE INHABITANTS ED THE RESIDENTIAL AREA CRISTINA MARY of the CANTON THE GUABO IN THE Year 2014 2015, happens in response to the employment status that the workers of the residential area selected, in a society that offers fat chance of job cross.